2016
DOI: 10.1042/bj20151029
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian homologue of yeast Afg1 ATPase (lactation elevated 1) mediates degradation of nuclear-encoded complex IV subunits

Abstract: Mitochondrial protein homeostasis is crucial for cellular function and integrity and is therefore maintained by several classes of proteins possessing chaperone and/or proteolytic activities. In the present study, we focused on characterization of LACE1 (lactation elevated 1) function in mitochondrial protein homeostasis. LACE1 is the human homologue of yeast mitochondrial Afg1 (ATPase family gene 1) ATPase, a member of the SEC18-NSF, PAS1, CDC48-VCP, TBP family. Yeast Afg1 was shown to mediate degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 30 publications
5
19
0
5
Order By: Relevance
“…The molecular mechanism of H 2 S toxicity is mainly the noncompetitive binding of its neutral form to the haem a3/CuB of the binuclear center within the COX I subunit, While it has been proposed that complex IV subunits cannot be the primary target of H 2 S in animals . COX IV is required for normal activity of complexes IV of the respiratory chain and COX IV is crucial for the stability and other subunits assembly of complex IV . In the present study, we have shown that COX I and COX IV expression significantly increase after administration 3 and 5 mg/kg NaHS.…”
Section: Discussionsupporting
confidence: 46%
“…The molecular mechanism of H 2 S toxicity is mainly the noncompetitive binding of its neutral form to the haem a3/CuB of the binuclear center within the COX I subunit, While it has been proposed that complex IV subunits cannot be the primary target of H 2 S in animals . COX IV is required for normal activity of complexes IV of the respiratory chain and COX IV is crucial for the stability and other subunits assembly of complex IV . In the present study, we have shown that COX I and COX IV expression significantly increase after administration 3 and 5 mg/kg NaHS.…”
Section: Discussionsupporting
confidence: 46%
“…Also, Lace1, which has been shown to participate in the degradation of Cox4 and Cox6a (Cesnekova et al . ), increased its abundance by more than two‐fold from P1 to P42.…”
Section: Resultsmentioning
confidence: 97%
“…The most enriched GO term from commonly down‐regulated genes in the PDX TA and DIA was mitochondrion ( Figure D). Many of the genes annotating to this category play a role in oxidative phosphorylation including Bcs1l , Rtn4lp1 (Nogo‐interacting mitochondrial protein), and Lace1 ( Figure E) . There were additional repressed genes that annotated to cytosol or membrane that play roles in energy metabolism, including Tfrc (transferrin receptor protein 1), which is a critical regulator iron uptake and Irs1 , which encodes an adapter protein and signal transducer for insulin‐mediated activation of the insulin‐like growth factor 1 receptor.…”
Section: Resultsmentioning
confidence: 99%